Indian Nuclear Exceptionalism and South Asian Strategic Stability - Anum A. Khan (CISS Insight Journal, 2023)
The nuclear non-proliferation and arms control regimes are ineffective due to prejudgment and a selective approach of NPT members. The treaty recognizes only certain countries as nuclear weapon states and has effectively divided the nuclear weapon states between “haves” and “have-nots.” This discrimination also extends to the supply of nuclear technology to India, a non-NPT nuclear weapon state (NWS). Inter alia, this special treatment to India will contribute to a lack of progress in achieving global nuclear disarmament. The Indo-US nuclear deal opened the Nuclear Suppliers Group’s (NSG) gateways for New Delhi. This is a unique example of double standards. It has not only placed global non-proliferation efforts in jeopardy but is also affecting strategic stability in South Asia. Another example of the West’s double standards is giving membership in the Missile Technology Control Regime (MTCR) to India. This paper offers a critical analysis of the inclination of Western states to promote their self-interests as opposed to playing their role in maintaining global peace and stability. Furthermore, the article discusses India’s commitment to the nuclear non-proliferation regime and the impact of exceptionalism on Indian foreign policy, affecting deterrence in South Asia.